ANALISIS POTENSI EKONOMI DALAM PEMBANGUNAN PERTANIAN KABUPATEN/KOTA DI PROVINSI JAWA BARAT - Riska Novitasari; Lies Sulistyowati; Maman H. Karmana (Universitas Galuh Ciamis, 2019)
Agriculture in West Java Province has great potential, but now the sector is not a leading sector. Therefore, the purpose of this study is to identify districts/cities in West Java which are region with an agricultural base, and identify region that play a role in spurring agricultural development in West Java Province. This research uses descriptive quantitative method, with the use of secondary data in the form of time series data from 2013-2017 for West Java GRDP and West Java districts/cities GRDP and their growth rates, and income per capita in West Java and income per capita districts/cities in West Java. While the analysis used is the analysis of Location Quotinet and Klassen Typology. The results of this study indicate that there are 14 districts/cities in West Java which are areas with an agricultural base, namely: Sukabumi, Cianjur, Garut, Tasikmalaya, Ciamis, Kuningan, Cirebon, Majalengka, Sumedang, Indramayu, Subang, West Bandung Regency, Pangandaran, and Banjar City. Based on the typology analysis, the class shows that the area with an agricultural base in West Java is only included in typologies 2, 3 and 4 which are region with high income but low growth, high growth but low income, and low growth and low income, so that those who can play a role in spurring agricultural development in West Java are districts/city with typology 2 which covers Cianjur Regency, Kuningan, Majalengka and West Bandung Regency.